Delayed Posterior Reversible Leukoencephalopathy Syndrome Triggered by FLOT Chemotherapy - Gandini, Jordi; Manto, Mario; Charette, Nicolas (Frontiers in Neurology, 2020)
Posterior reversible encephalopathy syndrome (PRES) is a potentially severe disorder of the autoregulation of cerebral perfusion. The major clinical manifestations are headache, seizures, altered mental status, and visual loss. The typical radiological finding is vasogenic edema predominating in the white matter of occipital and parietal lobes. PRES is increasingly recognized as a clinico-radiological entity owing to improvements and fast availability of brain imaging, especially magnetic resonance imaging (MRI). We present the exceptional case of a 67-year-old female patient with a gastric adenocarcinoma at stage IIB (T3N0M0) treated by FLOT chemotherapy (5-fluorouracil, oxaliplatin, docetaxel, and folinic acid). Two months after the unique administration of FLOT regimen, she developed sudden posterior headache and visual loss. Blood pressure values were normal. Cerebral tomography showed ischemic-like occipital bilateral lesions, and angiographic sequences revealed breakdown of the blood–brain barrier (BBB). MRI revealed bilateral parieto-occipital T1 hypointensity and T2 hyperintensity, which demonstrated vasogenic edema. The rest of the parts of the lesions were T1 hyperintensity, T2 hyperintensity, and diffusion-weighted imaging (DWI) hyperintensity, which indicate cortical laminar necrosis. After injection of gadolinium, a linear enhancement of the cortex was observed. She was treated with oral nimodipine. Follow-up was characterized by permanent visual sequelae and tetraparesis. PRES represents an urgent neurological condition. Our observation highlights that PRES should be considered in patients under chemotherapy, even when their blood pressure remains within normal range. This is the first report of PRES triggered by FLOT chemotherapy and with a silent window of 2 months between chemotherapy and PRES, widening further the spectrum of chemotherapy-induced PRES. Our case highlights the potential role of FLOT regimen in the pathogenesis of PRES and the need for a novel approach in terms of prevention of this potentially fatal complication when patients receive chemotherapy.